Daun Dewa (Gynura Pseudochina (Lour) Dc) Jelly Candy Making with Addition of Gelling Agents (Alginate, Carrageenan, And Gum Arabic) in Various Concentrations - Fesdila Putri Nurani; Pratiwi Eka Murliati; Dedin Finatsiyatull Rosida (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Jelly candy is generally made from fruit juice with some hydrocolloid addition in order to the gelling formation. The characteristic of jelly candy is a clear and transparent appearance with chewiness in texture. To increase its functional value, jelly candy can be added with various ingredients, for example, the extract of Daun Dewa (Gynura Pseudochina (Lour) Dc). Daun Dewa (Gynura Pseudochina (Lour) Dc) contains some active components such as alkaloids, flavonoids, essential oils, saponins, and steroids, triterpenoids, and tannins, where these compounds show antioxidant activity. One parameter on jelly candy making was the gelling formation influenced by the hydrocolloid or gelling agent's existence. Some gelling agent that has been used in commercial jelly candy-like alginate, carrageenan and Gum Arabic. The combination of those gelling agents with various concentrations would give the different characteristics of jelly candy. This study aimed to observe the characteristic of jelly candy with the addition of gelling agents and determine the best treatment that most liked by the panelists. The concentration of gelling agents used in this study was 0, 2.5%, 5%, 7.5%, and 10% (w/v) with a single factor of Simple Completely Randomized Design (CRD). The data analyzed using ANOVA. Based on the result, the best treatment of Daun Dewa jelly candy was made with the addition of 7.5% carrageenan and 2.5% gum Arabic that has moisture content value of 16.742%, ash content 0.685%, reducing sugar 20.273%, total phenol 11.078 mg TAE / gr, pH 4.27, gel strength 46.3788 N, antioxidant 32.536%, and sensory evaluation covering 4.96 for color, 4.28 for aroma, 4.60 for texture, and 4.88 for taste.